Interleukin-10 serum level in acute coronary syndrome patients (Medical Journal of Indonesia, 2009)
Aim To compare plasma IL-10 concentrations in patients with Acute Coronary Syndrome (ACS) with those in Coronary Artery Disease (CAD). Methods ACS patients hospitalized in intensive coronary care unit (ICCU) of Cipto Mangunkusumo Hospital/Faculty of Medicine University of Indonesia (CMH/FMUI), Persahabatan Hospital, MMC Hospital, and Medistra Hospital, Jakarta, between May 2005 and May 2006, were included in this study. The ambulatory CAD patients were taken as comparator. The serum IL-10 level was measured by immunoassay method, and compared by using Independent Student’s t-test. To investigate whether IL-10 serum level could predict ACS, the sensitivity and specificity of this parameter towards SKA in various IL-10 serum levels were calculated as well. Results In this observational study, as many as 146 subjects were analyzed, consisting of 84 ACS patients, and 62 coronary artery disease (CAD). The IL-10 level was higher in the group of ACS patients (7.37 pg/mL + 7.81, CI 95% 5.68-9.07) than that in CAD patients (1.59 pg/mL + 1.55, CI 95% 1.2-1.98). The optimal cut-off point for serum IL-10level is >1.95 pg/mL, with 79.76 % sensitivity and 77.42 % specificity. Conclusion The IL-10 level was higher in the ACS patients compared to that in CAD patients. Serum IL-10 measurement is a quite superior method to distinguish acute and stable condition, eventhough it is not as good as hsCRP for the same purpose. (Med J Indones 2009;18:165-9)